PROBLEMATIKA KEWARISAN AKIBAT PERKAWINAN TIDAK TERCATAT MENURUT HUKUM ISLAM DAN PERUNDANG-UNDANGAN - Taherong Taherong (Institut Agama Islam Negeri Bone, 2020)
AbstractThe result of this research show that recording of marriage became a crucial if there is a dispute, then the wife of the husband and wife in marriage the series does not have the legal power to ask for their rights because there is no document which proves that she is the wife of from si fulan. Maintaining the rights of the wife and children is an obligation, and one way of keeping these obligations were fulfilled is to record the wedding at KUA. Something that will make the obligation done perfectly then it becomes mandatory, then the recording of marriages in KUA is mandatory for the sake of safeguarding the rights of spouses and children. That is the law of their respective religions and beliefs that include provisions of legislation that applies to the religion and beliefs that all does not contradict or not specified in this Act.. Those who become victims (usually the wife) do not have the force of law to obtain its rights when faced with state law. The only way that reached through mediation, discussion is merely a consensus outside the courthouse.